The perceived effects of generational diversity on supervision of new professional nurses in public hospitals - Kholofelo L. Matlhaba (AOSIS, 2023)
Background: The current global nursing workforce is a combination of personnel from three different generation cohorts, which are the Baby Boomers, Generation X and Generation Y (Millennials). These generational cohorts work side by side to provide quality nursing care to the patients on a daily basis. Aim: This article aims to report the effects of generational diversity on the supervision of new professional nurses in selected public hospitals in North West province. Setting: This study was conducted at seven public hospitals situated at three out of the four districts of North West province, South Africa. These public hospitals classifications consist of six districts and one provincial hospitals. Methods: The study followed an exploratory, descriptive and contextual qualitative research design underpinning the constructivist paradigm was followed to pave a way for this study. Operational managers were purposively sampled and data were collected using the focus group discussion as well as individual interviews. Data analysis followed the guideline of the thematic analysis. Results: This article reports on three themes that emerged from data analysis, namely: (1) generational differences, (2) insubordination and (3) impact on supervision. Conclusion: Understanding the generational diversity and its impact on the supervision of new professional nurses might assist in improving the leadership styles for operational managers and will promote collegiality among colleagues and positively influence the provision of quality care for patients. Contribution: These results provide a framework for future research and provide the basis for understanding the impacts generational diversity has on supervision of new professional nurses.